2018
DOI: 10.1021/acs.jctc.8b00235
|View full text |Cite
|
Sign up to set email alerts
|

Nonlocal Electron–Phonon Coupling in Prototypical Molecular Semiconductors from First Principles

Abstract: A substantial amount of evidence indicates a relevant role played by the nonlocal electron-phonon couplings in the mechanism of charge transport in organic semiconductors. In this work, we compute the nonlocal electron-phonon coupling for the prototypical molecular semiconductors rubrene and tetracene using the phonon modes obtained from ab initio methods. We do not make the rigid molecular approximation allowing a mixing of intra- and intermolecular modes, and we use a supercell approach to sample the momentu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
69
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(80 citation statements)
references
References 51 publications
11
69
0
Order By: Relevance
“…single-point calculation) representation, and that non-local electron-phonon couplings could play an important role in these systems. 62,63 Device performance of computationally selected derivatives Using the information gleaned from the electronic structure calculations, compounds 3b-b and 3b-h were selected and evaluated for their performance in organic eld-effect transistors. Details on device fabrication can be found in the ESI.…”
Section: Computational Assessment Of Electronic Couplingsmentioning
confidence: 99%
“…single-point calculation) representation, and that non-local electron-phonon couplings could play an important role in these systems. 62,63 Device performance of computationally selected derivatives Using the information gleaned from the electronic structure calculations, compounds 3b-b and 3b-h were selected and evaluated for their performance in organic eld-effect transistors. Details on device fabrication can be found in the ESI.…”
Section: Computational Assessment Of Electronic Couplingsmentioning
confidence: 99%
“…Harmonic lattice dynamics calculations were then performed on the unstrained and strained structures to determine the normal modes and the corresponding frequencies according to established procedures based on the numerical evaluation of the Hessian matrix. [34][35][36] Available inelastic neutron scattering data for deuterated naphthalene 37 and theoretical calculations [38][39][40] have shown that the low-frequency (below 200 cm −1 ) phonon modes of molecular crystals feature a pronounced wave vector dependence. The effect of such phonon dispersion on e-ph coupling and on energetic disorder has been addressed only very recently.…”
Section: Crystal Structure and Lattice Dynamics Under Strainmentioning
confidence: 99%
“…Similarly, DFTB calculations performed in ref. yielded high percentage of the intramolecular motion in the LF vibrational modes of rubrene.…”
Section: Impact Of Molecular and Crystal Structure On Lf Vibrationsmentioning
confidence: 98%
“…The main technical challenge in DFT calculations of lattice phonons is relatively large size of the unit cell. As a result, the phonon dispersions have been accurately calculated only recently and only for small π‐conjugated molecules …”
Section: Lf Vibrations Electron–phonon Interaction and Charge Transmentioning
confidence: 99%
See 1 more Smart Citation